1997
DOI: 10.1111/1523-1747.ep12334249
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Cytoprotective Prostaglandin Synthase-1 by Minoxidil as a Possible Explanation for Its Hair Growth-Stimulating Effect

Abstract: Data from the literature indicate that nonsteroidal anti-inflammatory drugs (NSAIDs), such as indomethacin, naproxen, piroxicam, or ibuprofen, induce hair loss in vivo. These NSAIDs are well-known inhibitors of both the cytoprotective isoform of prostaglandin endoperoxide synthase-1 (PGHS-1) and of the inducible form (PGHS-2). By immunohistochemical staining, we found that PGHS-1 is the main isoform present in the dermal papilla from normal human hair follicle (either anagen or catagen), whereas PGHS-2 was onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 37 publications
4
50
0
2
Order By: Relevance
“…Interestingly, mPGES-1 expression in DP was reminiscent of the previously described specific DP COX-1 expression (13). mPGES-1 expression in DP was somewhat unexpected as it was generally coupled to that of COX-2, which was previously found absent in DP (13). One thus has to admit that mPGES-1 expression in hair follicle DP is coupled to COX-1 rather than to COX-2 expression, as recently observed in murine mammary gland (31).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Interestingly, mPGES-1 expression in DP was reminiscent of the previously described specific DP COX-1 expression (13). mPGES-1 expression in DP was somewhat unexpected as it was generally coupled to that of COX-2, which was previously found absent in DP (13). One thus has to admit that mPGES-1 expression in hair follicle DP is coupled to COX-1 rather than to COX-2 expression, as recently observed in murine mammary gland (31).…”
Section: Discussionsupporting
confidence: 53%
“…Immunological approach nevertheless revealed that mPGES-1 was strongly expressed in DP, a compartment which was usually absent in plucked hair follicles and whose contribution could not be evaluated in RT-PCR studies. Interestingly, mPGES-1 expression in DP was reminiscent of the previously described specific DP COX-1 expression (13). mPGES-1 expression in DP was somewhat unexpected as it was generally coupled to that of COX-2, which was previously found absent in DP (13).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In normal human skin, Müller-Decker et al (1999) reported the COX-2 protein expression in individual keratinocytes of the epidermis and hair follicles. However, according to Michelet et al (1997), COX-1 immunostaining was observed in the dermal papilla from human hair follicles, whereas COX-2 in the dermal papilla was expressed only in the anagen phase of the hair cycle. Although their findings appear to differ from ours, they actually might have observed expression in endothelial cells and fibroblast-like cells within the dermal papilla.…”
mentioning
confidence: 97%
“…Minoxidil, a reference treatment to stimulate hair regrowth, increases PGE 2 . Bimatoprost and latanoprost, PGF 2 α analogs, are recently used successfully to increase the length of eyelashes (6,8).…”
Section: Discussionmentioning
confidence: 99%